Effects of dietary methionine and cysteine restriction on plasma biomarkers, serum fibroblast growth factor 21, and adipose tissue gene expression in women with overweight or obesity: a double-blind randomized controlled pilot study - Olsen, Thomas; Øvrebø, Bente; Haj-Yasein, Nadia; Lee, Sindre; Svendsen, Karianne; Hjorth, Marit; Bastani, Nasser E.; Norheim, Frode; Drevon, Christian A.; Refsum, Helga; Vinknes, Kathrine J. (Journal of translational medicine, 2020)
Background Dietary restriction of methionine and cysteine is a well-described model that improves metabolic health in rodents. To investigate the translational potential in humans, we evaluated the effects of dietary methionine and cysteine restriction on cardiometabolic risk factors, plasma and urinary amino acid profile, serum fibroblast growth factor 21 (FGF21), and subcutaneous adipose tissue gene expression in women with overweight and obesity in a double-blind randomized controlled pilot study. Methods Twenty women with overweight or obesity were allocated to a diet low (Met/Cys -low, n = 7), medium (Met/Cys -medium, n = 7) or high (Met/Cys -high, n = 6) in methionine and cysteine for 7 days. The diets differed only by methionine and cysteine content. Blood and urine were collected at day 0, 1, 3 and 7 and subcutaneous adipose tissue biopsies were taken at day 0 and 7. Results Plasma methionine and cystathionine and urinary total cysteine decreased, whereas FGF21 increased in the Met/Cys -low vs. Met/Cys -high group. The Met/Cys -low group had increased mRNA expression of lipogenic genes in adipose tissue including DGAT1 . When we excluded one participant with high fasting insulin at baseline, the Met/Cys -low group showed increased expression of ACAC, DGAT1, and tendencies for increased expression of FASN and SCD1 compared to the Met/Cys -high group. The participants reported satisfactory compliance and that the diets were moderately easy to follow. Conclusions Our data suggest that dietary methionine and cysteine restriction may have beneficial effects on circulating biomarkers, including FGF21, and influence subcutaneous adipose tissue gene expression. These results will aid in the design and implementation of future large-scale dietary interventions with methionine and cysteine restriction. Trial registration ClinicalTrials.gov Identifier: NCT03629392, registration date: 14/08/2018 https://clinicaltrials.gov/ct2/show/NCT03629392 .